UPCYCLING USED JEANS IN OUTWEAR DESIGN : UPCYCLING USED JEANS IN OUTWEAR DESIGN - Tersinaningsih, Rily; Indah Pratiwi, Diah (Universitas Sarjanawiyata Tamansiswa, 2025)
The aims of this study are 1) to determine and describe the upcycling process of fashion making outerwear by utilizing used jeans, and 2) to develop used jeans products into creative outerwear products. The method in this study uses the Gustami art creation model which includes three stages including 1) the exploration stage, namely collecting visual references, design ideas, and material studies on used jeans that are suitable for use; 2) the design stage, in the form of making three outwear design sketches with sustainable fashion characteristics, then a selection is carried out to choose the most suitable design for production; 3) the realization stage, namely the realization of the selected design into an outwear product using used jeans as the main material. Validation of the work is carried out through a structured interview method using an assessment rubric format, involving experts. The results of this study are expected to contribute to the development of sustainable fashion design and become a reference in textile waste management through a creative and functional approach.